Efforts to Protect and Prevent Sexual Abuse of Children - Syam, Andi Fatmawati; Ichsan, Nursyamsi; Nasir, Citra (Cendekiawan Indonesia Timur, 2022)
The rise of sexual abuse cases against minors is alarming to society. How could it not be that children who are the next generation of this nation are damaged in their infancy. In addition, people also become restless and worried about the security that exists in the environment around their children. This shows that children have not received protection for security in their daily lives. Thus, through the socialization of state constitutional policies in the protection and prevention of sexual violence against women and children in Palopo City, families no longer ignore the mentality of adolescents and only focus on the material needs of children. Efforts to prevent sexual violence against children are carried out through socialization on how to prevent sexual violence against children, including 1) parents conducting open communication and establishing emotional closeness with children. 2) Parents are advised to provide children with an understanding of their bodies and things that other people should not do to their body parts, as well as the involvement of law enforcement officials. However, PTPAS faces obstacles in efforts to prevent sexual violence against children; namely, children cannot understand the motives of the perpetrators of sexual violence, so the vital role of parents and adults who are around children is to have intensive communication with children